STUDY ON PRODUCTION AND MARKETING PATTERNS OF MILK SUPPLY IN MUZAFFARABAD CITY, AZAD JAMMU AND KASHMIR - M.Z.U. Khan; A.U. Khan; F.M. Khattak; Saima; M.I. Anjum; Z.H. Kuthu; Z. Naseer (Journal of Animal and Plant Sciences, 2008)
In order to assess the production and marketing patterns of milk in Muzaffarabad city, the capital of Azad Jammu and Kashmir, an investigation was undertaken by randomly interviewing the farmers in three zones of the area. For this purpose, a total of 569 farmers (producers), 86 middlemen and 45 retailers were interviewed and information was recorded. It was observed that out of 569 farmers 333 (58.52 percent) were literate and 236 (41.48 percent) were illiterate. During survey it was observed that in three zones of the area all types of dairy animals; buffaloes, cows and goats were kept. In zone II and III, bullocks were kept in addition to buffaloes, cows and goats for land ploughing. The results of the study indicated that middlemen earned more profit than the producers and retailers. Middlemen earned Rs 0.63/liter in zone I, Rs. 2.23/liter in zone II and Rs. 2.64/liter of milk in zone III. The retailer earned equal amount from three zones i.e. Rs. 1.67/liter of milk because of the retailer stationed in the city. Whereas the producers who invested for enterprise earned Rs 3.44/liter in zone I, Rs. 1.44/liter in zone II and Rs. 0.44/liter of milk in zone III. The statistical analysis showed that there were non-significant difference among the net margins of the producers, middlemen and retailers.
Keywords: Marketing pattern; net margins; retailers; survey.